Minimum landing size in European eel fisheries management: limitations of simplistic management approaches in a semelparous species. (21st June 2016) - Pohlmann, Jan-Dag; Freese, Marko; Hanel, Reinhold
Abstract : In light of the critical stock situation of the European eel a careful evaluation of management regulations is crucial. The use of minimum landing size (MLS) is a commonly adapted management measure, though it is questionable whether it can sufficiently increase escapement in order to meet management objectives, especially in a semelparous species like the European eel. In this study, a simple age-based escapement model was used in order to describe the effects of minimum landing size on escapement and yield, with particular reference to different fishing intensities for yellow and silver eels (i.e. fishing regime). Resulting model predictions show that MLS is only a suitable tool in European eel fisheries management if it is flanked by additional management measures, such as catch quotas or effort controls. It is further demonstrated that the efficiency of MLS is largely depending on the underlying fishing regime, emphasizing the need for the collection of respective data.